Korelasi Motivasi Mahasiswa dalam Mengikuti Perkuliahan Terhadap Perencanaan Karier - Sari, Kurnia (Jurnal Fokus Konseling, 2018)
Students are at the stage of the final teenage development task. At this stage, one of the teenagers developmental tasks is to choose, prepare to run a job and make career planning. Career selection requires more careful preparation and planning than just getting a temporary job. Career planning is influenced by career development which is a series of changes that occur at every level of life. Student Motivation in Participation It is an encouragement from students to follow lectures in accordance with their wishes, their wills, and be able to see their interests, talents and ability to plan for the future. Based on the calculation results obtained that the correlation shows the probability 0.000 <0.05. This means that there is a significant relationship between student motivation in following the lecture with career planning.Keywords: Motivation, Career Planning